Individual memory performance was predicted by a subset of iEEG signal components. - Adam J. O. Dede (11554007) (2025)
All scatter plots display significant relationships between individual-level signal components and memory performance. The x-axis displays the difference between the value of the signal component on hit minus miss trials. The y-axis represents behavioral memory performance (d’). Points represent means across channels within each participant. Red triangles indicate participants whose removal would result in the p value rising from below .05 to between .05 and .10. Relationships for which removal of any single participant caused the p value to rise above .1 are not shown. The signal component displayed along the x-axis of each plot is indicated by its title. A.i Signal component aligned to image onset during encoding that predicted memory performance A.ii Signal components aligned to HFB peaks during encoding that predicted memory performance. This panel can be regenerated using data contained in allSig.csv and code in allSig.Rmd [112]. B. Signal components aligned to image onset during retrieval that predicted memory performance. Note that ITPC at image onset, dlPFC ITPC, and dlPFC-PHG connectivity were important at both encoding and retrieval. This panel can be regenerated using data contained in allSig.csv and code in allSig.Rmd lines 376–460 [112].